2005
DOI: 10.1179/016164105x17288
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid superoxide dismutase and serum malondialdehyde levels in patients with aneurysmal subarachnoid hemorrhage: preliminary results

Abstract: These preliminary results suggest that the levels of antioxidants are decreased after the onset of SAH in the early period, possibly because of increased oxidative stress. Reactive oxygen-mediated oxidative damage may play an important role in inflammation after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Oxidative stress has been proven to play a crucial role in the pathophysiological process after SAH. 1,10,14 It has been demonstrated that excessive reactive oxygen species and reactive nitrogen species including hydroxyl radical, superoxide anion, H 2 O 2 , nitric oxide, and peroxynitrite are generated early after SAH, and consume enzymatic and nonenzymatic antioxidant defense systems. 1,20 Moreover, these free radicals will lead to neuronal damage by promoting lipid peroxidation, protein breakdown, and DNA damage, and this in turn leads to cellular apoptosis, endothelial injury, and BBB permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress has been proven to play a crucial role in the pathophysiological process after SAH. 1,10,14 It has been demonstrated that excessive reactive oxygen species and reactive nitrogen species including hydroxyl radical, superoxide anion, H 2 O 2 , nitric oxide, and peroxynitrite are generated early after SAH, and consume enzymatic and nonenzymatic antioxidant defense systems. 1,20 Moreover, these free radicals will lead to neuronal damage by promoting lipid peroxidation, protein breakdown, and DNA damage, and this in turn leads to cellular apoptosis, endothelial injury, and BBB permeability.…”
Section: Discussionmentioning
confidence: 99%
“…1,10,14 Given that there is substantial evidence for significant levels of oxidative stress following SAH and for the beneficial effects of antioxidant therapy in experimental SAH and clinical trials, the use of free-radical scavengers is a reasonable approach in the treatment of SAH.…”
mentioning
confidence: 99%
“…Several studies have suggested that dietary antioxidants may play a protective role against the development of subarachnoid hemorrhage (SAH) (Marzatico et al, 1998;Leppala et al, 1999Leppala et al, , 2000Hirvonen et al, 2000;Kaynar et al, 2005;Okamoto, 2006;Okamoto and Horisawa, 2006). In general, various dietary antioxidants may be interactive or synergistic rather than isolated.…”
Section: Introductionmentioning
confidence: 99%
“…1 Before moving into clinical trials, however, we need to address the possible brain oxidative stress related to HBO because extensive oxidative stress has been reported in SAH animal models, 2 in SAH patients, 3 and application of HBO may potentiate an existing oxidative stress after SAH. Three groups of contradicting reports of HBO in oxidative stress have been published; they state that HBO at pressures higher than 4 atmospheres absolutes (Ͼ4 ATA) increases oxidative stress, 4 but at a lower atmosphere (Յ3 ATA) does not enhance oxidative stress.…”
mentioning
confidence: 99%